2008
DOI: 10.1007/s12221-008-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational differences of color sensation and preference for naturally dyed fabrics

Abstract: This study was performed in order to evaluate subjective color sensation and preference for yellowish and reddish natural dye fabrics and to provide meaningful objective colorimetric properties which can quantify the sensation and preference focused on intergenerational differences. Among lots of natural dye silk fabrics, four differently dyed fabrics for each hue were used as specimens by cluster analysis. College students as younger generation and high school teachers as middle-aged evaluated them subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…“To prefer” means to like the most and preferences are based on taste as well as on visual, tactile, auditory and olfactory signals. Visual aesthetics is considered to be the primary factor affecting preference 1 . People show specific preferences towards different aspects of their surroundings; some prefer certain colours, and specific shapes, patterns and textures to others 2 .…”
Section: Introductionmentioning
confidence: 99%
“…“To prefer” means to like the most and preferences are based on taste as well as on visual, tactile, auditory and olfactory signals. Visual aesthetics is considered to be the primary factor affecting preference 1 . People show specific preferences towards different aspects of their surroundings; some prefer certain colours, and specific shapes, patterns and textures to others 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Clothing and textiles coloured with natural dyestuffs are attracting considerable commercial attention, because the desire for expression of personality based on sensibility and wellbeing has increased along with the growing needs of eco‐friendly fashion . Because clothing and textiles dyed with natural dyestuffs are well known for their antimicrobial properties, researchers have studied fabrics dyed with natural dyestuffs in order to develop related products . Sensibility research covers a variety of fields including phycology, engineering, design, textiles and colour research .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Reported literature also includes color sensory evaluation of mostly yellowish and reddish natural-dyed substrates. [22][23][24] However, these studies do not include persimmon-dyed fabrics, which range, in hue, from yellow to red and include toning grayish or dull colors. 25,26 Considering the cultural importance of Galchon in Korea, and its color range and unique place in fashion, it was considered worthwhile to conduct a crosscultural evaluation of observers' emotional response to a range of persimmondyed and mordanted substrates and correlate these against colorimetric attributes of these substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that considerable differences exist among cultures pertaining to emotional connotations of, and preference for color, especially among fashion experts and students . Reported literature also includes color sensory evaluation of mostly yellowish and reddish natural‐dyed substrates . However, these studies do not include persimmon‐dyed fabrics, which range, in hue, from yellow to red and include toning grayish or dull colors .…”
Section: Introductionmentioning
confidence: 99%